ANALYSIS OF ARABICA COFFEE CULTIVATION PRACTICES IN SIPIROK BY COFFEE FARMERS IN SIPIROK - Desy Army Lestari Siregar; R. Hamdani Harahap; Irfan Simatupang; Zulkifli Lubis; Bengkel; Yudhi Ramadani Harahap (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
Coffee is a major commodity in Sipirok, South Tapanuli Regency, with potential national and international markets. The implementation of Good Agricultural Practices (GAP) in coffee cultivation is still limited, resulting in suboptimal quality and competitiveness of Sipirok coffee. This study aims to analyse farmers' knowledge, attitudes, and practices (KAP) towards GAP and examine local government policies supporting coffee development. It also aims to identify challenges and barriers to GAP implementation. The theoretical foundations used include Pierre Bourdieu's habitus theory, the KAP model, and Rogers' innovation adoption theory. This study employed a qualitative method with a descriptive approach through field observations, in-depth interviews, and literature studies. Data validation was performed using triangulation techniques. The study area covered three sub-districts in South Tapanuli: Sipirok, Arse, and Saipar Dolok Hole. The results showed that most farmers still rely on traditional practices passed down through generations and have not fully understood or implemented GAP. The main inhibiting factors are limited capital, limited access to information, and resistance to change. A small group of farmers and local companies have adopted GAP more effectively. Local government policies are considered suboptimal in providing farmer education and mentoring. This study confirms that the transformation towards GAP implementation requires structural and institutional support, as well as changes in farmer habits to enable Sipirok coffee to compete in the global market. This study shows that the adoption of Good Agricultural Practices (GAP) by coffee farmers in Sipirok remains low and partial. In terms of knowledge, most farmers are not yet systematically familiar with GAP and still rely on inherited traditions. In terms of attitudes, they demonstrate caution towards new practices, with doubts persisting because GAP is considered expensive, difficult to implement, and does not guarantee better prices. In practice, most farmers are still at the pre-GAP stage and are GAP literate. Comprehensive implementation is only seen in groups fostered by institutions such as the Darul Mursyid Islamic Boarding School. Keywords: Sipirok Coffee, Good Agricultural Practices, Analysis of Cultivation Practices, Coffee Farmers, Habitus